2019
DOI: 10.1021/acsbiomaterials.8b01145
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropylcellulose Coating to Improve Graft-to-Bone Healing for Anterior Cruciate Ligament Reconstruction

Abstract: Anterior cruciate ligament (ACL) injury is one of the most common injuries in sports, and ACL reconstruction with an artificial ligament is a good treatment for quick recovery. However, current artificial ligaments made of polyethylene terephthalate (PET) are still associated with some problems due to the hydrophobic nature and low biological induction activity of PET. Many efforts have been used to improve the biocompatibility of PET in recent years, and our previous work has shown that surface modification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…The anterior cruciate ligament (ACL) is most vulnerable to sports injuries ( Yang et al, 2019 ). Compared to the limited effect of conservative treatment in the healing of torn ACLs, the surgical intervention aims to restore knee stability and reduce degeneration changes found in ACL-deficient knees.…”
Section: Introductionmentioning
confidence: 99%
“…The anterior cruciate ligament (ACL) is most vulnerable to sports injuries ( Yang et al, 2019 ). Compared to the limited effect of conservative treatment in the healing of torn ACLs, the surgical intervention aims to restore knee stability and reduce degeneration changes found in ACL-deficient knees.…”
Section: Introductionmentioning
confidence: 99%
“…The coating can improve the hydrophilicity of PET fibers, which is beneficial to cell proliferation and tissue ingrowth. The literature indicates that these biocompatible polymers, such as collagen, silk fibroin, and hydroxypropyl cellulose, have been widely used in the surface modification of PET fibers. This series of coatings has been proven to improve the biocompatibility of PET ligaments to a certain extent. In recent years, researchers have tried to enhance the biological activities of the coatings by loading growth factors into them to improve their capability of promoting osteogenic differentiation of stem cells/osteoblasts in the host bone tunnel, enhancing bone tunnel healing and integrating graft–bone interface.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, a number of methods aiming to improve the biocompatibility and osteogenic activity of PET artificial ligaments have been extensively studied. Among those studies, the most common strategy is to modify bioactive coatings to the surface of PET fiber, such as collagen, silk fibroin, and hydroxypropyl cellulose. Although those coatings can improve the hydrophobicity of PET ligament and the adhesion and growth of the cells cultured on the surface of PET, they still need to be further improved to enhance their osteogenic activity. In recent studies, some researchers revealed that doping inorganic mineral in the coatings, such as nanohydroxyapatite and bioglass, can improve their capability for promoting osteogenic differentiation of biomineralization-inspired magnesium silicate composites (BMSCs) and inhibiting fibrous scar tissue formation at the graft–bone interface. However, those coatings were usually prepared by dispersing the inorganic mineral or nanoparticle in the biopolymer solution and then cross-linked on the surface of PET.…”
Section: Introductionmentioning
confidence: 99%
“…enhanced the biocompatibility of PET artificial ligaments for ACLR by applying a hydroxypropylcellulose (HPC) coating. [ 134 ] The HPC‐coated PET ligaments exhibited improved cell growth, adhesion, and osteogenic differentiation capability compared to uncoated PET ligaments, as demonstrated in vitro and in a beagle dog model. The HPC coating significantly improved cytocompatibility and graft‐to‐bone healing, making it a promising approach for ACLR using PET artificial ligaments.…”
Section: Application Of Nondegradable Polymer Synthetic Materials In ...mentioning
confidence: 99%